Length-Weight Relationship and Condition Factor of Siganus Lineatus around Kareko waters, Lembeh Strait - Sampouw, Mouren V.; Salaki, Meiske S.; Moningkey, Ruddy D.; Rangan, Jety K.; Pratasik, Silvester B.; Watung, Juliaan (Sam Ratulangi University, 2022)
AbstractThis study aims to determine the relationship between length and weight and condition factors of Siganus lineatus around Kareko waters, Lembeh Strait. Sampling was carried out in March 2021 from fishermen's catch using net fishing gear. There were 31 individuals collected with a length range of 169.95-345.69 mm and a weight range of 94-939 grams. The relationship between length and weight of male (b= 0.3018), female (b= 0.3631) and total (b= 0.3287) showed a negative allometric growth pattern. Mean condition factors of the male, female and total were 0.106, 0.075, and 0.091, indicating that rabbitfish are in poor condition.Keywords: rabbitfish; allometric; fishermen.AbstrakPenelitian ini bertujuan untuk mengetahui hubungan panjang berat dan faktor kondisi Siganus lineatus di perairan sekitar Kelurahan Kareko, Selat Lembeh. Pengambilan sampel sepanjang bulan Maret 2021 dariÂ hasil tangkapan nelayan yang menggunakan alat tangkap jaring. Jumlah ikan yang terkumpul sebanyak 31 individu dengan kisaran panjang 169,95-345,69 mm dan berat 94-939 gram. Hubungan panjang berat ikan beronang jantan (b= 0,3018), betina (b= 0,3631) dan total (b= 0,3287) menunjukkan pola pertumbuhan alometrik negatif. Faktor kondisi rata-rata ikan beronang jantan, betina dan total yaitu 0,106, 0,075 dan 0,091, hal ini menunjukkan ikan beronang dalam kondisi kurang baik karena memiliki nilai kurang dari satu.Kata kunci : ikan beronang; alometrik; nelayan.